An Efficient and Sustainable Approach to Decarboxylative Cross-Coupling Using Silica Coated Magnetic Copper Nanocatalyst for the Synthesis of Internal Alkynes - Yadav, Manavi; Srivastava, Anju; Gaur, Rashmi; Gupta, Radhika; Arora, Gunjan; Sharma, Rakesh Kumar (Frontiers in Chemistry, 2022)
A highly efficient magnetically separable copper nanocatalyst has been developed for decarboxylative cross-coupling reaction for the alkynylation of aryl halides using alkynyl carboxylic acid as a reaction partner. The chemical nature, morphology, size, and magnetic properties of the prepared nanocatalyst were studied by SEM, TEM, EDS, FT-IR, VSM, and ICP techniques. Remarkably, this catalyst represents the first successful copper based heterogeneous system for this type of coupling that provides a low-cost, stable, and environmentally friendly magnetically recoverable entity that can be re-used for multiple runs without appreciable loss in its catalytic activity.